Dynamic and Fatigue Life Prediction Analysis of Airfield Runway Rigid Pavement Using Finite Element Method - K. Kavin Mathi; K Nallasivam (Computational Engineering and Physical Modeling, 2022)
The significance of rigid airfield pavements is growing as airline travel becomes more sophisticated. Apart from the geometrics of runway design, an efficient runway should satisfy structural aspects. In this connection, greater emphasis should be placed on pavement slab analysis and design. The research analyzes the dynamic analysis of a 3-dimensionally formed concrete slab resting on a subgrade foundation, which is a homogeneous, isotropic elastic half-space model, in order to assess the performance of variation in Young's modulus in compared to Winkler's reaction modulus. The influence and impact of two distinct landing gear configurations, especially tridem and tandem-dual wheels of the A-380 and A-310, on varying slab structural parameters such as concrete's modulus of elasticity, slab thickness, and temperature gradients are explored. The aircraft load stresses are evaluated using the finite element programme ANSYS APDL 2021R2 version, which models the slab as a 3-D element with an 8-noded-solid 185 element type. The above-mentioned pavement models' modal and dynamic (transient) analyses were performed for different take-off speeds, and a comparison is conducted for the present standard strength and high strength concrete types. Miner's rule and the Rainflow counting technique are used to estimate the fatigue life based on the findings of the transient analysis. The fatigue life for high-strength concrete is found to be 50% more. The fatigue life is 36% higher for the A-380 load, indicating that a material's fatigue property is entirely determined by its load frequency rather than its magnitude.